Assessing capacity in cases of fluctuating decision-making ability. (13th August 2020) - Griffith, Richard
Abstract : Richard Griffith, Senior Lecturer in Health Law at Swansea University, considers the law on decision-making capacity and recent approaches to the assessment of fluctuating capacity by the Court of Protection